Ionospheric chaos in the solar quiet current due to sudden stratospheric warming events across the European and African sectors - I. A. Oludehinwa; I. A. Oludehinwa; A. Velichko; O. I. Olusola; O. S. Bolaji; O. S. Bolaji; N. Marwan; B. O. Ogunsua; B. O. Ogunsua; A. N. Njah; T. O. Ologun (Nonlinear Processes in Geophysics)
This study examines the ionospheric chaos in the solar quiet current, Sq(H), across European and African sectors during 2009 and 2021 sudden stratospheric warming (SSW) events. The SSW was categorized into precondition, ascending, peak, descending, after-, and no-SSW phases based on the rising stratospheric temperature. 13 magnetometer stations, located within the geographical longitude of 26 to 40° across European and African sectors were considered. The magnetometer data obtained during the periods of SSW were used to derive the solar quiet current time series. This solar quiet current time series was transformed into a complex network using the horizontal visibility graph (HVG) approach, and fuzzy entropy (FuzzyEn) was applied to the resulting node-degree time series to quantify the presence of chaos or orderliness behavior in the ionosphere during SSW. The results revealed that the latitudinal distribution of entropy in the European sector depicts high entropy values, indicating the presence of ionospheric chaos. Consistent low entropy values unveiling the presence of orderliness behavior were found to be prominent in the African sector. This dominance of orderliness behavior during the phases of SSW in the African sector reveals that the SSW effect manifest orderliness behavior on the regional ionosphere of the African sector, while the pronounced features of ionospheric chaos found in the European sector reveal evidence of significant effects of SSW on the regional ionosphere in this sector. Finally, we found that after the peak phase of SSW, the ionospheric chaos is more pronounced.